Applying translabial ultrasound to detect synthetic slings—You can do it too! A comparison of urology trainees to an attending radiologist. Issue 7 (10th February 2017) - Shen, Jim K.; Faaborg, Daniel; Rouse, Glenn; Kelly, Isaac; Li, Roger; Alsyouf, Muhannad; Myklak, Kristene; Distelberg, Brian; Staack, Andrea
Abstract : Aims: Translabial ultrasound (TUS) is a useful tool for identifying and assessing synthetic slings. This study evaluates the ability of urology trainees to learn basic pelvic anatomy and sling assessment on TUS. Methods: Eight urology trainees (six residents and two medical students) received a lecture reviewing basic anatomy and sling assessment on TUS followed by review of two training cases. Next, they underwent a 126‐question examination assessing their ability to identify anatomic planes and structures in those planes, identify the presence of slings, and assess the location and intactness of a sling. The correct response rate was compared to that of an attending radiologist experienced in reading TUS. Non‐parametric tests (Fisher's exact, chi‐squared tests, and Yates correction) were used for statistical analysis, with P  < 0.05 considered significant. Results: 847/1008 (84.0%) of questions were answered correctly by eight trainees compared to 119/126 (94.4%) by the radiologist ( P  = 0.001). The trainees' correct response rates and Fisher's exact test P values associated with the difference in correct answers between radiologist and trainee were as follows: identification of anatomic plane (94.4%; P  = 0.599), identification of structure in sagittal view (80.6%; P  = 0.201), identification of structure in transverse view (88.2%; P  = 0.696), presence of synthetic sling (95.8%; P  = 1.000), location of sling along the urethra in (71.5%; P  = 0.403), intactness of sling (82.6%; P  = 0.311), and laterality of sling disruption (75.0%; P  = 0.076). Conclusions: Urology trainees can quickly learn to identify anatomic landmarks and assess slings on TUS with reasonable proficiency compared to an experienced attending radiologist.